Psychological treatments for the mental health symptoms among individuals infected with COVID-19: a scoping review protocol. Issue 3 (2nd March 2023) - Sugita, So; Hata, Kotone; Takamatsu, Naoki; Kimura, Kentaro; Gonzalez, Lecsy; Kodaiarasu, Krandhasi; Miller, Christian; Umemoto, Ikue; Murayama, Keitaro; Nakao, Tomohiro; Kito, Shinsuke; Ito, Masaya; et al.
Abstract : Introduction: Mental health symptoms such as depression, anxiety and sleep problems are commonly observed in individuals suffering from acute COVID-19 infection to post-COVID-19 syndrome. Studies have provided preliminary evidence for the efficacies of cognitive behavioural therapy, mindfulness-based interventions, acceptance and commitment therapy, and many other treatments for this population. Although there have been attempts to synthesise the literature on these psychological interventions, previous reviews have been limited in terms of the sources, symptoms and interventions that they included. Furthermore, most studies reviewed were conducted in early 2020, when COVID-19 had only recently been classified as a global pandemic. Since then, substantial research has been conducted. As such, we sought to provide an updated synthesis of the available evidence of treatments for the range of mental health symptoms associated with COVID-19. Methods and analysis: This scoping review protocol was developed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. Systematic searches were carried out on scientific databases (PubMed, Web of Science, PsycINFO and Scopus) and clinical trial registries (ClinicalTrials.gov, WHO ICTRP, EU Clinical Trials Register and Cochrane Central Register of Controlled Trials) to identify studies that have or will assess the efficacy or any aspects of psychological treatment for acute to post-COVID-19 syndrome. The search was conducted on 14 October 2022 and identified 17 855 potentially eligible sources/studies published since 1 January 2020 (duplicates removed). Six investigators will independently carry out titles and abstract screening, full-text screening and data charting and the results will be summarised using descriptive statistics and narrative synthesis. Ethics and dissemination: Ethical approval is not required for this review. The results will be disseminated through a peer-reviewed journal, conference presentations and/or academic newspapers. This scoping review has been registered with Open Science Framework (https://osf.io/wvr5t ).